Odpowiedzi

Najlepsza Odpowiedź!
2010-02-19T16:51:18+01:00
(-3,6)×4/9=
= -36/10 × 4/9 = -4/10 × 4 = -8/10 = -0,8

(-2,1)×(-4 2/7)=
= -21/10 × (-30/7) = -3/10 × (-30) = -3 × (-3) = 9

-⅞:(-5,6)=
= -7/8 ÷ (-56/10) = -7/8 × (-10/56) = -1 × (-10) = 10

9/10:(-3/4)=
9/10 × (-4/3) = 3/10 × (-4) = -12/10 = -1,2

(-1½):(-0,06)=
-3/2 ÷ (-6/100) = -3/2 × (-100/6) = -1/2 × (-50) = 25

(-2⅔):1,2=
-8/3 ÷ 12/10 = -8/3 × 10/12 = -2/3 × 10/3 = -20/9

⅔:(-6)=
= 2/3 × (-1/6) = -1/9

(-0,45):1⅘=
= -45/100 ÷ 9/5 = -45/100 × 5/9 = -5/100 × 5 = -25/100 = -0,25

(-2,75):(-2,2)=
-275/100 ÷ (-22/10) = -275/100 × (-10/22) = 275/220 = 5/4 = 1,25

(-3,5):(-1⅖)=
= -35/10 ÷ (-7/5) = -35/10 × (-5/7) = 5/2 = 2,5
6 3 6
2010-02-19T16:57:56+01:00
-1.6
9
0.49
-1.2
25
-2 2/9
-1/9
-0.25
1.25
2.5

2 1 2
2010-02-19T17:07:48+01:00
* -16/10
* 9
*5/32
*-6/5
*25
*-20/9
*-1/9
*-1/5
*55/44
*5/2
1 1 1